Mobile Distributed News Web Service - Abdul Wahab, Prasit (2005)
The demand for access to the Internet by mobile users is increasing. Many mobile providers have to provide the wireless network carries signals between the cellular phone and web server. A new concept is latest released that joined mobile and web service together called “Mobile Web Service”. It provides services like service on web sites but use both web and mobile device as clients. This research aim to explore mobile web service technology and attempt to develop a prototype called “Mobile Distributed News Web Service System” which demonstrates the usefulness of mobile web service technology. This study uses online news website as a case study.